2003
DOI: 10.1086/367679
|View full text |Cite
|
Sign up to set email alerts
|

Why Dowry Payments Declined with Modernization in Europe but Are Rising in India

Abstract: In contrast to most dowry-oriented societies in which payments have declined with modernization, those in India have undergone significant inflation over the last five decades. This paper explains the difference between these two experiences by focusing on the role played by caste. The theoretical model contrasts caste-and non-caste-based societies: in the former, there exists an inherited component to status (caste) that is independent of wealth, and in the latter, wealth is the primary determinant of status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
182
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(188 citation statements)
references
References 53 publications
5
182
1
Order By: Relevance
“…Similarly, it has been suggested that the decline in fertility that has accompanied economic development in India may have contributed to a worsening of gender bias, as the desired number of sons may have decreased less quickly than the desired total number of children (Das Gupta and Bhat (1995), Basu (1999)). Anderson (2003) constructs a model where economic development, in a caste-based society, leads to an increase in dowries. This might lead to an increase in son preference.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been suggested that the decline in fertility that has accompanied economic development in India may have contributed to a worsening of gender bias, as the desired number of sons may have decreased less quickly than the desired total number of children (Das Gupta and Bhat (1995), Basu (1999)). Anderson (2003) constructs a model where economic development, in a caste-based society, leads to an increase in dowries. This might lead to an increase in son preference.…”
Section: Introductionmentioning
confidence: 99%
“…A formal model, in which these two countervailing forces act so as to determine equilibrium family size and composition, is developed in section 2. From this we argue that a reason why Muslims have larger families than Hindus is that, …rstly, they may not desire sons as much as Hindus 3 and, secondly, that they may be less apprehensive, compared to Hindus, of having daughters. In consequence, not only do Muslims have larger families than Hindus, but they also have relatively more daughters than sons.…”
Section: Introductionmentioning
confidence: 92%
“…A large empirical literature has examined gender di¤erentials in marriage in India [Mukhopadhyay 2000;Kapadia 2000] and marriage-related issues such as dowry [Anderson 2003;Sen 1998;Deolalikar and Rao 1998], but there is less discussion of this issue in the context of religion. Gender biases have been investigated extensively [Kishor 1993; Krishnaraj, Sudarshan and Shari¤ 1998; Murthi, Guio and Dreze 1995; Bhat and Zavier, 2003], with particular emphasis on the unequal distribution of food and health-care allocations between sons and daughters in India.…”
Section: Son Preference Daughter Aversion and The Demand For Childrenmentioning
confidence: 99%
“…These models aim to disentangle the forces hypothesized to be responsible for the origins of the FGMo trait (virginity assurance [Buss 1989] and/or costly signaling [Grafen 1990;Zahavi 1975]) from those that cause its persistence in contemporary populations (frequency dependence [McElreath et al 2008]). Ross et al (2015) contend that the practice of FGMo can be understood as arising from the constraints of marriage markets in much the same way as bridewealth and marriage payments (Anderson 2003;Bell and Song 1994;Borgerhoff Mulder 1995;Chiappori et al 2002). During the origins of FGMo, parents may have chosen to subject their daughters to the practice in order to ensure and signal their virginity, and thus enhance their marriageability, especially to high-status marriage partners.…”
Section: Evolutionary Accounts Of Fgmo Emergence Transmission and Pmentioning
confidence: 99%